An assessment of regional sustainability via the maturity level of entrepreneurial ecosystems - Tatyana Olegovna Tolstykh; Leyla Ayvarovna Gamidullaeva; Nadezhda Shmeleva; Maciej Woźniak; Sergey Mikhailovich Vasin (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Despite the prominence of sustainable development approaches in the academic literature, together with the significance attributed to the economy and society, the concept is not sufficiently theorized, especially in terms of methodological issues. The presented study makes a contribution to the academic literature by providing a synthesis on territorial sustainable development research and related concepts of innovation and entrepreneurial ecosystems (EE). We propose a methodological framework for the assessment of regional sustainability, replicating and expanding the approach of D. Isenberg, and draw inference to the impact of institutional environments on the maturity level of EEs. We present our assumptions in the example of two entrepreneurial ecosystems in Russia and Poland (the Penza region and the Małopolska region) with relevant interpretations, which enable us to gain a comprehensive understanding of how to progress in sustainable entrepreneurial ecosystem development. The results of this analysis provides information to help academics, policymakers, government, and business owners with a more in-depth understanding of the practical mechanisms that support absorption of the EE model to achieve Sustainable Development Goals.
Keywords: 650; open innovation; sustainable development; ecosystem maturity; entrepreneurial ecosystems; innovation ecosystem; region; territory